Effects of N-fertilizer application and density on tiller and yield of rice in cold area - WANG Xiu-zhi; QIAN Yong-de; L Ü Yan-dong; LIU Li-hua; ZHENG Gui-ping (浙江大学学报. 农业与生命科学版, 2011)
To investigate the effect of fertilization factors and density on rice tiller and yield in cold area, the effect of N-fertilizer dosage at different stages, application stage of regulating fertilizer (RF) and hole spacing (HS) on rice yield, yield components and tiller was discussed by using the method of multiple factors quadratic rotation-regression-orthogonal combination design. The conventional japonica rice variety Kenjiandao 10 was used as test material. The results showed that the amount of N-fertilizer in earlier stage had the greatest effect on the tiller, and the next was HS and the application stage of RF, and the third was mutual effect of N-fertilizer application in earlier stage and other factors; Meanwhile, the correlation analysis between each factor of tiller and yield showed that the sequence for the yield effect was effective tiller rate > formation of spike from the tillers number > maximum tiller number > mutual effect of effective tiller rate and spike rate of population> mutual effect of maximum stem number and spike rate of population. Thus, according to actual production, especially in low-temperature and earth cooling year, appropriately increasing the amount of N-fertilizer applied in earlier stage with proper density and other agronomic measures which could promote early growth and quick tillering of tiller, was an effective way for increasing yield of rice in cold area.